Microencapsulation of Fucoxanthin by Water-in-Oil-in-Water (W/O/W) Double Emulsion Solvent Evaporation Method: A Review - Noviendri, Dedi (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2014)
Fucoxanthin is a major xanthophyll present in brown seaweeds such as Sargassum binderi, S. duplicatum, Turbinaria turbinata, Padina australis, Undaria pinnatifida and Hijkia fusiformis. This carotenoid has a unique structure including oxygenic functional group such as, two hydroxy, keto, epoxy (5,6-monoepoxide), and an allenic bond. Fucoxanthin has some anticancer activities such as, exhibits inhibitory property on colon cancer cells and human hepatic carcinoma HepG2 cell line. This xanthophyll also induces apoptosis of human leukemia cancer HL-60 cells, human prostate cancer PC-3 cell, human lung cancer H1299 cell line etc. Unfortunately, the poor solubility of this carotenoid in water hinders it to be a drug candidate. Fucoxanthin is also a pigment that is sensitive to temperature and light. One of the possible ways to circumvent the problem with light and temperature is by microencapsulating it. Microencapsulation (ME) in biodegradable polymers, e.g. poly(D,L-lactic-co-glycolic acid) (PLGA) is a promising approach to protect any potential drug from rapid degradation. Solvent evaporation method is the most popular technique of preparing PLGA microsphere (MS) and this technique has been extensively studied in recent years for the preparation of MS. In the water-in-oil-in-water (w/o/w) double emulsion solvent evaporation method, stability of the primary emulsion (PE) is a critical factor. When the PE is unstable, encapsulation efficiency (EE) is low. Stability of PE can be enhanced by including emulsifying agent or stabilizers such as polyvinyl alcohol (PVA). The presence of a stabilizer/ emulsifier plays a significant role in influencing particle size (PS), external morphology of microsphere and colloidal stability. Â